Ballooning Bureaucracy: Tracking the Growth of High-Skilled Administration within Swedish Higher Education - Fredrik Andersson; Henrik Jordahl; Anders Kärnä (Research Institute of Industrial Economics (IFN), 2021)
Organizations, both non-profit and for-profit, needs to allocate labor for both production as well as internal administration. If this allocation is skewed towards internal administration, organizations, and especially non-profit organizations, might develop sclerosis over time with too much labor allocated to internal administration compared to production. Using detailed registry data on all individuals working at Swedish universities and colleges, we document a rapid increase in the number of qualified administrators, both in the number of employees and in total wages paid for these. This increase is not present in less qualified administration, and is mainly driven by an increase by a few professions such as communication and human resources. The increase does not lead to a significant reduction, or increase, in the time that researchers and teachers spend on administration. This in turn suggests that Swedish higher education over-allocates resources to high-skilled administration.
Keywords: P16; L25; 330; Organization theory; Sclerosis; Productivity Growth; Bureaucracy; Higher education